Advice From Former-Smoking E-Cigarette Users to Current Smokers on How to Use E-Cigarettes as Part of an Attempt to Quit Smoking. Issue 8 (3rd August 2017) - Russell, Christopher; Dickson, Tiffany; McKeganey, Neil
Abstract: Introduction: Substitution of e-cigarettes for tobacco smoking has the potential to prevent almost all the harm caused by smoking. Identifying strategies that may increase smokers' capability, opportunity and motivation to use e-cigarettes in place of tobacco cigarettes is vital. Former smokers who have successfully used e-cigarettes to quit smoking may be especially well qualified to increase current smokers' interest in switching and ability to switch to e-cigarettes. Methods: A multi-national, self-selected sample of 4192 former smokers who quit smoking by using e-cigarettes were asked, via an online survey, the advice they would offer to smokers who are considering using e-cigarettes to support an attempt to quit smoking. Results: Thematic analysis of participants' qualitative responses identified four emergent themes: (1) Find a combination of vaping device, flavors of e-liquid and nicotine strength that "works for you"; (2) Continuing to smoke for a while after starting to vape is OK; (3) Failure to quit smoking with the use of approved smoking cessation aids before success with e-cigarettes is common; and (4) Awareness of improved health and hygiene since switching to vaping. Conclusions: Experienced vapers who used to smoke appear eager to give smokers advice and practical information about vaping that may assist attempts to switch from smoking to vaping. Encouraging cigarette smokers to interact with experienced vapers in places where vapers themselves once received advice and now give advice about vaping—vape shops and online discussion fora—may have significant potential to help more smokers to switch to e-cigarette use. Implications: This study describes the advice that former-smokers who used e-cigarettes to quit smoking would offer to smokers who are considering using an e-cigarette to support an attempt to quit smoking. Vapers advised smokers to find the right combination of device, flavors and nicotine strength, continue to smoke and vape for a while if they wished, not be deterred by past failed attempts to quit smoking, and expect health to improve after they have switched to vaping. Encouraging smokers to interact with vaping peers in vape shops and in online vaping-dedicated discussion fora may help significantly more smokers switch to vaping.